Antioxidant and antibacterial activity of Acorus calamus. L leaf and rhizome extracts - Kho See Li; Chan Sook Wah (Jurnal Gizi Klinik Indonesia, 2017)
Background: Acorus calamus (sweet flag) is a well-known traditional herb used in India. There were only limited studies done on both hydrophilic and hydrophobic extracts of A. calamus and the biological activities of phenolic and flavonoid compounds as well as alpha-asarone in the sweet flag.Objective: The present study was designed to explore the antioxidant and antibacterial activities of both hydrophilic and hydrophobic of A. calamus leaf and rhizome extracts. Lastly, the correlation between the biological activities and total phenolic content (TPC), total flavonoid content (TFC) as well as total alpha-asarone content (TAC) of three different extracts (water, hexane and methanol extracts) was revealed.Method: TAC was determined through using HPLC method, while TPC and TFC were determined through spectrophotometric method. DPPH-free radical scavenging assay (DPPH-FRS) and ferric reducing power assay (FRAP) were used to analyze antioxidant activity, whereby disc diffusion method was used to analyze the antibacterial activity.Results: Methanol extracts had significantly (p<0.05) highest levels of antioxidant activities, antibacterial activity TPC (4.466%1; 3.603%2) and TFC (12.819%1; 7.411%2) content. The significant (p<0.05) highest TAC was observed in hexane extracts (0.762%1; 2.975%2). TPC (p<0.05; r=0.855) and TFC (p<0.05; r=0.855) correlated to FRAP, while DPPH-FRS solely correlated to TFC (p<0.05; r=0.873).Conclusion: Both of the hydrophilic and hydrophobic extracts of A. calamus could be potent antioxidant agents for nutraceutical application and antibacterial agent for food application. Lastly, flavonoids and phenols extracted from sweet flag could be a good potent source of antioxidants for nutraceuticals or food additives as those compounds are correlated to the antioxidant activity.1 Leaf extract; 2Rhizome extract